Studies in natural products chemistry : Vol. 50 - Rahman, Atta-ur-, 1942- (Amsterdam, Netherlands : Elsevier, 2016)
Natural products in the plant and animal kingdom offer a huge diversity of chemical structures that are the result of biosynthetic processes that have been modulated over the millennia through genetic effects. With the rapid developments in spectroscopic techniques and accompanying advances in high-throughput screening techniques, it has become possible to isolate and then determine the structures and biological activity of natural products rapidly, thus opening up exciting opportunities in the field of new drug development to the pharmaceutical industry. This series covers the synthesis or testing and recording of the medicinal properties of natural products, providing cutting edge accounts of the fascinating developments in the isolation, structure elucidation, synthesis, biosynthesis and pharmacology of a diverse array of bioactive natural products.
4 -- Anticancer and Antineurodegenerative Effects of Ginsenosides.
Includes index.
Online resource; title from PDF title page (ScienceDirect, viewed October 6, 2016).
Includes bibliographical references and index.
Keywords: Bioorganic chemistry; Bioactive compounds; Natural products; SCIENCE -- Life Sciences -- Biochemistry; Bioorganic chemistry; Bioactive compounds; Natural products; Electronic books